1999
DOI: 10.1097/00006534-199910000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Composite Tissue Allografts in Rats: IV. Graftversus-Host Disease in Recipients of Vascularized Bone Marrow Transplants

Abstract: This laboratory has used a composite tissue allograft model as a vehicle for studies on a new type of bone marrow transplant, the vascularized bone marrow transplant. The model consists of a rat hind limb transplant that incorporates integumentary musculoskeletal, and lymphopoietic tissues. These transplants, in comparison with conventional marrow transplants, have the advantage of providing a syngeneic microenvironment and immediate engraftment of both mature and progenitor hemopoietic cells at the time of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 8 publications
0
18
0
1
Order By: Relevance
“…[82][83][84] This observation could be explained by the fact that a very small amount of active BM is expected to be transferred with this type of CTA. 79,80,85 Furthermore, since the first successful transplantation of BM in humans in 1968, 86 much progress has been made in clinical use as well as in experimental models to treat non-life-threatening conditions through hematopoietic reconstitution. The extension of lower-risk protocols, such as the "non-total body irradiation" approach, to establish the state of mixed chimerism across MHC barriers seems to be an important point to reduce the toxicity occurring from the conditioning of the host.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[82][83][84] This observation could be explained by the fact that a very small amount of active BM is expected to be transferred with this type of CTA. 79,80,85 Furthermore, since the first successful transplantation of BM in humans in 1968, 86 much progress has been made in clinical use as well as in experimental models to treat non-life-threatening conditions through hematopoietic reconstitution. The extension of lower-risk protocols, such as the "non-total body irradiation" approach, to establish the state of mixed chimerism across MHC barriers seems to be an important point to reduce the toxicity occurring from the conditioning of the host.…”
Section: Resultsmentioning
confidence: 99%
“…A possible disadvantage of transplanting a limb allograft with functional immune effector cells is the potential for these mature allogeneic T cells to attack the recipient's tissue, resulting in the serious clinical reaction GVHD. 79 In 1990, Hewitt et al used rat hind limb transplantation to evaluate the involvement of VBMT in inducing GVHD. They observed that approximately 35% to 40% of the recipients developed GVHD when parental Lewis rat hind limbs were transplanted to Lewis ϫ Brown Norway F1 hybrids.…”
Section: Tolerance and Chimerismmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies by our laboratory have used this VBMT model to demonstrate that the development of low-level, stable mixed lymphocyte chimerism after limb allografting is associated with alloimmune tolerance induction, while unstable, high-level lymphocyte chimerism is associated with the development of graft-versus-host disease (GVHD). 32,[74][75][76][77][78][79] The work of Lee and associates 80 in Boston concerning tolerance induction has also been instrumental in the field of CTA. They have been successful in inducing long-term tolerance to vascularized musculoskeletal allografts in major histocompatibility complex-matched, minor antigenmismatched pigs after only a 12-day postoperative course of cyclosporine A. Lee has also used intrathymic injection of donor-derived bone marrow cells along with the short-term use of an anti-lymphocyte serum to prolong survival of skin allografts in rats.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,13-15 A microsurgically transplanted hind limb allograft contains bone marrow tissue, which is an immunomodulatory factor that facilitates allograft tolerance 15,16 ; the allograft also contains lymph nodes, neurovascular structures, muscle, cartilage, tendon, ligament, and skin, which is accepted as the most antigenic tissue of the body. 17,18 Allogeneic hind limb transplantation is technically complex and leaves the recipient with a functional deformity.…”
mentioning
confidence: 99%